(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
In this paper the author reflects on the constitutional rights at the end of life, distinguishing between those who have a sure constitutional foundation, such as the right to not suffer and the right to refuse therapeutic treatments even life-saving, and the claims of dignified death like euthanasia, with respect to which the Constitution does not say in a binding way, and the choice – between right and crime – should be reserved for the democratically elected legislator.